Absorption, distribution, metabolism and elimination of 14C-ETX0914, a novel inhibitor of bacterial type-II topoisomerases in rodents. (2nd January 2017) - Guo, Jian; Joubran, Camil; Luzietti, Ricardo A.; Basarab, Gregory S.; Grimm, Scott W.; Vishwanathan, Karthick
Abstract: 1. ETX0914 is a novel bacterial topoisomerase inhibitor that has a novel mode-of-inhibition and is in clinical development for the treatment of infections caused by Neisseria gonorrhoeae . 2. The in vitro biotransformation studies of ETX0914 using mouse, rat, dog and human hepatocytes showed moderate intrinsic clearance in mouse and rat and low intrinsic clearance in dog and human. 3. Following intravenous administration of [ 14 C]-ETX0914 in rats, the mean recovery of administered dose in urine, bile and feces was approximately 15%, 55% and 24%, respectively. Unchanged ETX0914 recovered in urine and bile was less than 5% of the dose, indicating that ETX0914 underwent extensive metabolism in rats. Metabolites M1, M2, M4, M6 and M12 detected in both rat and mouse urine samples were not detected in mouse urine when predosed with 1-aminobenzotriazole, indicating that these metabolites were cytochrome P450 mediated products. The major fecal metabolites observed in rats were not formed when ETX0914 was incubated with fresh feces from germ free rats under sterile condition or in incubations with rat intestinal microsome and cytosol, suggesting that most likely ETX0914 was directly excreted into gut lumen where metabolites were formed as intestinal microflora-mediated products. The major sites of metabolism by CYP enzymes were in the morpholine and oxazolidinone rings while it was benzisoxazole reduction with the gut microflora.